Seismic Protection of Buildings in Areas Adjacent to Open-Pit Mining - Palyvoda, Oleksandr; Skachkov, Andriy; Zhukov, Serhiy; Yermolenko, Dmytro (International Journal of Engineering and Technology, 2018)
Purpose of the present research is the analysis of the seismic loadings on buildings in areas adjacent to open-pit mining, depending on the patterns of the spatial concentration of explosive energy in the rock massif, which have a complicated structure and its acoustic anisotropy; the justification for the general approach to technological solutions for the protection of buildings and structures and determination of the limits for parameters of mass explosions in open-pits due to the parameters of their seismic influence on these objects. The main factors of anthropogenic seismic regime of mining towns under conditions of application of exploding geo-technologies are analysed. The analysis of the change of the stress state of rock massifs with respect to their structure and lithological composition; the concept of the simulation model for the propagation of seismic waves in anisotropic medium and the formation of waveguides and shielding fractures in it; statistical analysis of surveying observations and mathematical treatment of their results are considered. As a result of the carried out researches, methods of calculating seismic safe restrictions for the parameters of blasting operations in the open pit and the protection of the built-up areas by shielding fractures have been developed.Â Â